Econometric modeling of panel data on the saving patterns of Philippine agricultural households - Alberto, Angelo M. 1989- (2011)
Abstract (This study mainly aims to identify significant determinants of Philippine agricultural households panel data model, the study estimates two econometric models which determine the relationship of agricultural saving with said determinants. As the focus of this study is on agricultural households, another focus of this study is to consider expenses on durable goods as part agricultural households saving. Results indicate that age, self-employment of household saving. Self-employment, however, is significant only in the original definition of saving, which does not involve expenses on durable goods. In addition, time and cross-section fixed effects suggest that there are certain years and regions which has less agricultural households saving. Such findings have important implications on not only agricultural households themselves, but also Philippine economy and the possible actions of regulatory bodies concerned).
Vita.
Thesis (M.A. Statistics)--University of the Philippines, Diliman.
Keywords: Agricultural households -- Philippines-